Modelo compreensivo para saúde mental dos professores da educação básica: os papéis da atenção plena, regulação emocional, autocompaixão e sentido de vida - Santos, Karine David Andrade (2023)
Basic Education professionals are subject to numerous psychosocial risks, mainly, during the exercise of their teaching activity. Literature has reported the emergence of different psychic disorders in teachers of this level of education, and among them are burnout syndrome, a psychopathology that represents the end result of different forms of stress, and common mental disorders (CMDs), bringing labor turnover and harm to the teaching-learning process. To prevent and promote mental health, in this professional audience, the meaning of life has been shown to be an effective resource, especially when faced with circumstances of unavoidable suffering, providing an improvement in regulatory emotional skills. The increment of this variable can be enhanced by mindfulness and self-compassion practices, as, by recognizing and accepting their challenging internal experiences, the individual has room for a more meaningful life or to have meaning in life, thus demonstrating a potential relationship between mindfulness, self-compassion and meaning in life. In view of the theoretical aspects outlined, this thesis had the general objective of structuring the impact of the relationships between mindfulness, self-compassion, emotional regulation and meaning in life, on mental health in Basic Education teachers of the state public network of the city of Aracaju and northern region of Bahia, segmented into the following specific objectives: a) to understand the experience of self-compassion, the meaning in life and the mental health of teachers of Basic Education in the state public school system, in the municipalities of Aracaju and in the northern region of interior of Bahia; b) investigate the relationships between mindfulness, self-compassion, emotion regulation strategies and meaning of life for each burnout syndrome profile in Basic Education teachers in the state public school system, in the municipalities of Aracaju and in the northern region of interior of Bahia; c) investigate the relationships between mindfulness, self-compassion, emotion regulation strategies and meaning of life for MAD (mild anxiety disorder) and MDD (mild depressive disorder) in Basic Education teachers in the state public school system, in the municipalities of Aracaju and in the northern region of interior of Bahia. For theoretical deepening, this thesis elaborated seven chapters, distributed in two sections: in the first, four theoretical ones were arranged and, in the second, three integrative reviews. Section I includes a theoretical overview of the main variables of the thesis: mental health, meaning in life, self-compassion and mindfulness, organized into four chapters. Chapter 1 aimed to present the prevalence and main reasons related to CMDs, concepts about professional burnout and factors related to the manifestation of this syndrome, in Basic Education teachers; Chapter 2 was intended to present the main concepts of logotherapy and the relationship between meaning in life and mental health; Chapter 3 aimed to describe the history, concepts, instruments, mechanisms and results of research on self-compassion and Chapter 4 aimed to present history, concepts and measures, mechanisms, results and care, in interventions in mindfulness and the application of mindfulness interventions for teachers. Section II, composed of integrative reviews, sought to systematize studies on protective factors in teachers' mental health, that is, meaning in life, self-compassion and mindfulness, in three chapters. Chapter 5 aimed to investigate the relationship between meaning in life (MIL) and mental health in teachers, whose findings indicated that meaning in life is negatively associated with burnout syndrome and perceived stress and provides better rates of psychological functioning and vital satisfaction in students. teachers; Chapter 6 aimed to describe and examine the results of studies on self-compassion and meaning in life, whose conclusions indicated that a positive association between meaning in life and self-compassion enables subjective well-being and positive outcomes in mental health; Chapter 7 aimed to describe and examine the results of mindfulness interventions for burnout syndrome in teachers, indicating a predominance of MBSR (Mindfulness Based Stress Reduction) programs and an increase in the mental health levels of the participants, whose training included modules of selfcompassion, compassion and emotion regulation. Finally, after the theoretical structuring of the thesis, section III presented the results of empirical studies, contemplating the specific objectives of the thesis. Chapter 8 contemplated the first specific objective of the thesis, whose results obtained by the IRaMuTeQ software indicated that the classroom, working conditions and individual aspects affect the quality of mental health of these workers who, on the other hand, have the educational process as a source of existential fulfillment. Chapter 9 met the second specific objective of the thesis, indicating, by regressive model, that the frenetic profile is explained by self-compassion and a facet of mindfulness; the findings of structural equation modeling (SEMs) indicated that, for the under-challenged profile, the general self-compassion factor covariated negatively with the search for meaning in life, a variable with a positive relationship for this type of professional burnout. The same statistical analysis, conducted for the worn-out profile, showed that the general self-compassion factor covariated, in a positive way, with the presence of meaning in life, a variable with a negative association with this mental health outcome. Finally, chapter 10 contemplated the third specific objective of this work, pointing out, through the regressive model, that TAL is explained by self-compassion and by some facets of mindfulness; the TDL, through the ESM calculations, the general selfcompassion factor positively impacted the presence of meaning in life, which, in turn, is negatively associated with the outcome in question. It is concluded that this thesis contemplated the proposed objectives, since significant results were found, involving self-compassion, in particular, and meaning in life in the workers surveyed. These findings are an advance, at a theoretical and epistemological level, as they bring together variables from different but complementary theoretical bases, namely: logotherapy and cognitive-behavioral therapy (CBT). It is a path that signals which variables should be considered in future studies on mental health, in particular, burnout, TAL and TDL, in Basic Education teachers from the state public network.